Analisis Faktor-Faktor Keberhasilan Implementasi Transformasi Digital: (Systematic Literature Review (SLR)) - Misbahuddin Misbahuddin; Dita Fitriani Juliasari (Journal of Management and Creative Business, 2026)
Digital transformation has become a strategic priority for organizations to improve competitiveness, operational efficiency, and business agility. However, despite increasing investments in digital technologies, many transformation initiatives fail due to organizational and human-related challenges rather than technological limitations. This study aims to identify and synthesize the critical success factors (CSFs) influencing the successful implementation of digital transformation and information systems. The research employed a Systematic Literature Review (SLR) using identification, screening, eligibility, and synthesis stages. Relevant articles were retrieved from Scopus, ScienceDirect, Springer, Emerald, and IEEE using keywords related to digital transformation, critical success factors, ERP implementation, information systems success, and the People–Process–Technology framework. Based on predefined inclusion and exclusion criteria, 20 peer-reviewed articles were selected for analysis. The findings indicate that the most influential success factors include top management support, digital leadership, employee engagement, user involvement, effective communication, team capability, organizational readiness, technology readiness, data quality, and transformation process. The review further reveals that successful digital transformation depends not only on technological readiness but also on organizational processes and human factors. Among these, top management support and user involvement consistently emerge as the most significant determinants of success. Furthermore, the People–Process–Technology (PPT) framework provides a comprehensive perspective for explaining the interrelationships among these critical success factors. This study concludes that organizations should adopt a holistic digital transformation strategy by integrating leadership, organizational culture, business processes, human resource capabilities, and technology readiness. Balancing the People–Process–Technology dimensions is essential for increasing the likelihood of successful digital transformation and achieving sustainable competitive advantage.